2017
DOI: 10.1155/2017/4018470
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and Coping Strategies of the Saudi Nursing Students in the Clinical Training: A Cross‐Sectional Study

Abstract: Nursing students often encounter high levels of stress through clinical practice that may cause psychological or emotional problems during their professional life eventually affecting the quality of patient care they provide. The aims of the current study were to identify the level and types of stress perceived by nursing students in their clinical practice and to identify the coping strategies that students used to relieve their stress. A descriptive, cross-sectional design was used in this study. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
30
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 24 publications
11
30
3
Order By: Relevance
“…This study found that there is a significant differences between some demographic variables and overall perceived stress level among students as age, gender, family income and students worked in night shifts, some studies agreed with current results while other studies declared that this positive significant were found only between level of stress and age (Chan et al, 2009;Shaban et al, 2012) [31,32] In disparate to these finding study done in Saudi Arabia (2017) also found no significant differences in stress with regard to gender among undergraduate students [33].…”
Section: Discussionsupporting
confidence: 73%
“…This study found that there is a significant differences between some demographic variables and overall perceived stress level among students as age, gender, family income and students worked in night shifts, some studies agreed with current results while other studies declared that this positive significant were found only between level of stress and age (Chan et al, 2009;Shaban et al, 2012) [31,32] In disparate to these finding study done in Saudi Arabia (2017) also found no significant differences in stress with regard to gender among undergraduate students [33].…”
Section: Discussionsupporting
confidence: 73%
“…While there are prevalent studies on stress and coping strategies worldwide, little research is available on stress levels and coping styles of nursing students in Saudi Arabia. From the researcher's knowledge, only the study of Hamaideh, Al-Omari, and Al-Modalla, and Alsaqri have investigated the phenomenon [15,16]. Hamaideh, Al-Omari, and Al-Modalla found that clinical training has been recognized as a stressful experience for nursing students.…”
Section: Research Articlementioning
confidence: 99%
“…At present, nursing education in Saudi Arabia receives surprisingly little attention in research in terms of clinical practice. Several studies showed that Saudi students have been found to encounter stress levels above the mean where assignments and workloads are the most common sources [16]. Anxiety during clinical exposures has been identified as a primary reason for student nurses' intent to leave the BSN program.…”
Section: Introductionmentioning
confidence: 99%